Phytochemicals Analysis and Antioxidant (IC50) Value of Dried and Fresh Mangrove (Rhizopora racemosa) Leaves Extract for Herbal Drink Base: Analisis Fitokimia dan Antioksidan (IC50) Ekstrak Daun Kering dan Basah Mangrove (Rhizopora racemosa) Sebagai Bahan Dasar Minuman Herbal - Adi Prayitno, Sutrisno; Utami, Dwi Retnaningtyas; Putri, Silvy Novita Antrisna (jurnal makanan tropis dan teknologi agroindustri, 2025)
The use of mangrove leaves as a functional ingredient is associated with secondary metabolites such as steroids, saponins, tannins, phenols, flavonoids, antioxidants, magnesium, sodium, potassium and calcium. This research determined the total phenol content (TPC), total flavonoid content (TFC) and antioxidants (IC50) in dry and fresh mangrove leaf infusion extracts. The method used was infusion extraction. The materials used are fresh mangrove leaves and dried leaves (dried in the oven). The data obtained then discussed descriptively based on the average obtained in the calculations. The research results showed that the type or condition of leaves used has an influence on TPC, TFC and Antioxidants (IC50). Oven drying can produce higher levels of secondary metabolites compared to fresh leaf infusion (TPC, 36 mg GAE/g; TFC 4.12 mg QE/g; IC50 225,706 ppm). Dried leaf extraction has better potential in producing secondary metabolic compounds and antioxidants. The choice of extraction method and type of solvent is highly recommended for further research objectives, because it suits research interests. It is recommended that when making functional drinks (tea) from mangrove leaves, to add other sources of ingredients such as dried lemon or mint leaves so that the resulting flavor is fresher and provides a better linking assessment of preferences.